2012
DOI: 10.1002/ls.1206
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fluid inertia forces on the squeeze film characteristics of conical plates—ferromagnetic fluid model

Abstract: On the basis of the Shliomis ferromagnetic fluid model, this paper is mainly concerned with the influences of convective fluid inertia forces in magnetic fluid-based conical squeeze film plates in the presence of external magnetic fields. By applying the averaged momentum principle, a lubrication equation governing the film pressure is derived. Some previous contributions can be obtained from special cases of the present studies. Comparing with the non-inertia non-magnetic case, better squeeze film performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…The results derived from Vadher et al [32] in the case of non-conducting plates agrees with the results presented here to a good degree in the sense that the load carrying capacity in both the cases differ by 0.013%. Even if, Shliomis ferromagnetic model was used in Lin et al [33], the load carrying capacity observed there and the load carrying capacity found here, do not defer much at least in the case of the negatively skewed roughness especially, when negative variance is involved. This article suggests that the roughness and the angle of the cone of the conical bearing must be given due consideration while designing the bearing system even if there is the presence of a strong magnetic fluid.…”
Section: Resultscontrasting
confidence: 55%
See 1 more Smart Citation
“…The results derived from Vadher et al [32] in the case of non-conducting plates agrees with the results presented here to a good degree in the sense that the load carrying capacity in both the cases differ by 0.013%. Even if, Shliomis ferromagnetic model was used in Lin et al [33], the load carrying capacity observed there and the load carrying capacity found here, do not defer much at least in the case of the negatively skewed roughness especially, when negative variance is involved. This article suggests that the roughness and the angle of the cone of the conical bearing must be given due consideration while designing the bearing system even if there is the presence of a strong magnetic fluid.…”
Section: Resultscontrasting
confidence: 55%
“…Besides, the conductivity also increased the load carrying capacity. Lin et al [33] analyzed the effects of fluid inertia forces on the squeeze film characteristics of conical plates with ferromagnetic fluid model. This discussion was mainly, concerned with the influences of convective fluid inertia forces in Shliomis model based ferromagnetic squeeze film in conical plates.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the increasing fluid velocity, the effects of fluid inertia forces need to be included in the study of FFs‐lubricated squeeze films. In this respect, lots of work based on Shliomis model has been done by Lin and his colleagues . According to their results, the effects of fluid inertia forces were found to yield an increase in the load capacity and to prolong the approaching time for the FFs sphere‐plate system in the presence of transverse magnetic field.…”
Section: Ferrofluids Lubrication Based On Three Flow Modelsmentioning
confidence: 99%
“…In this respect, lots of work based on Shliomis model has been done by Lin and his colleagues. [67][68][69] According to their results, the effects of fluid inertia forces were found to yield an increase in the load capacity and to prolong the approaching time for the FFs sphereplate system in the presence of transverse magnetic field. Furthermore, for the squeezing circular plates is a special case of squeeze film between conical plates, the squeeze film characteristics of FFs-based conical plates including fluid inertia force is of interest.…”
Section: Ferrofluids Lubricationmentioning
confidence: 99%
“…A squeeze film has a lot of different applications in automobile and domestic appliances. That is why, researchers like (Bhat and Deheri 1991, Lin et. al.…”
Section: Introductionmentioning
confidence: 99%